2013
DOI: 10.1109/jqe.2013.2250255
|View full text |Cite
|
Sign up to set email alerts
|

YDFL Operating in 1150–1200-nm Spectral Domain

Abstract: -The family of the YDFLs operating in the range of 1147-1200 nm with the output power up to 35 W was realized. The ASE was analyzed and its origin was discussed in the frames of the inhomogeneous broadening concept; the parameter K describing ASE was introduced.Index terms -Optical fiber lasers, optical fiber materials, fluorescence spectroscopy, infrared spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The reflectivity of the LR-FBG was high enough to ensure maintaining of the tuning range of pump power as high as 60 W without arising PL within the "conventional" Yb 3+ band (see above). For the same reason, the YDF was heated up to 40 • C [16,28]. Furthermore, to diminish the thermal shift of the gratings' Bragg wavelengths, they were mounted on aluminum heat dissipaters; this allowed us to minimize the spectral shift of the laser peak wavelength lesser than 1 pm per 1 Watt of laser power.…”
Section: Laser Setup and Basic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflectivity of the LR-FBG was high enough to ensure maintaining of the tuning range of pump power as high as 60 W without arising PL within the "conventional" Yb 3+ band (see above). For the same reason, the YDF was heated up to 40 • C [16,28]. Furthermore, to diminish the thermal shift of the gratings' Bragg wavelengths, they were mounted on aluminum heat dissipaters; this allowed us to minimize the spectral shift of the laser peak wavelength lesser than 1 pm per 1 Watt of laser power.…”
Section: Laser Setup and Basic Characteristicsmentioning
confidence: 99%
“…However, a disadvantage inherent to LW-YDFLs is that laser signal in this case competes with a strong amplified spontaneous emission (ASE) arising within the "conventional" spectral band, ~1060 to 1100 nm [16,28], due to a very high gain in YDF in this spectral range as compared that inherent to LWs. Moreover, the higher pump power, the stronger ASE signal is; so with increasing pump power above some critical level, CW parasitic lasing (PL) arises at some wavelength within this spectral band [28,29] when a high YDF gain gets compensating a high-level loss of the parasitic cavity formed by weak reflections from the laser-cavity components and fiber splices. With pump power growth, the efficiency of lasing at a LW drops due to both the increase of ASE spectral density and PL power.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that most of the published literatures for YDFL focus on the common wavelength band such as 1070-1080 nm, whose operating power can achieve kilowatt level without too much difficulty. Because of the much smaller relative net gain and the significant amplified spontaneous emission at common band, lasing at 1120-1200 nm band (which also locates in the emission region of Yb-doped silica fiber) is much more challenging [53][54][55][56][57][58] . Nevertheless, lasing at 1120-1200 nm band could find tremendous applications including biomedicine, new-style pump sources and remote sensing.…”
Section: Tandem-pumped High-power Nfamentioning
confidence: 99%
“…For instance, in 2009, diode-pumped YDFL with a maximum output power of 18 W at 1154 nm was reported, whose slope efficiency was 50%, which also showed the advantages of fiber heating on suppressing the ASE [24]. In 2013, Dvoyrin et al reported a diode-pumped YDFL at 1160 nm with 21 W output power and 1147 nm with 35 W output power, the slope efficiency was 60% and 52%, respectively [25].…”
Section: Introductionmentioning
confidence: 99%